Effective quotation for custom products based on virtual supply chain configuration - Li, Qun (2012)
Customization has become a key strategy for sustainable competitiveness for many Fortune 500 companies. Intensifying competition has been pushing companies to make more varieties of products to meet various customer needs and launch new products continuously with shorter product life cycles. To survive in this kind of rapidly changing market environment, companies strive to produce a large variety of products while managing supply chain efficiently and controlling costs effectively. Many companies in the technology sector, like Dell and HP, are faced with increasing challenges to manage assemble-to-order (ATO), make-to-order (MTO) or engineer-to-order (ETO) supply chains to achieve near mass production efficiency. Within the circumstance of ATO/MTO/ETO supply chain management, an interesting topic of research is how manufacturers can generate quotations accurately and efficiently in response to customer requirements. To secure business from potential customers for custom products, it is very critical for companies to have accurate and fast quotation response generation methods that can help them to meet customer requirements in terms of cost target, delivery schedule, customer location and product specification details. Moreover, globalization and market competition have driven modern manufacturing enterprises to collaborate with a large number of partners in their supply chain to design, manufacture and ship their products to end customers. Outsourcing enables enterprises to grow beyond national boundaries and to leverage capabilities and resources worldwide. Thus, a complex global ATO/MTO/ETO mass customization supply chain network is formed and integrates a large number of business entities which are inter-related in the process of decision-making, procurement, fabrication, assembly, logistics and distribution activities associated with various families of products. The large number of varieties involved in supply chain activities and the geographically dispersed suppliers and facilities locations pose a great challenge to managing these supply chain networks. With the advance of information and telecommunication technologies, those geographically dispersed supply chain partners and facilities can be linked together virtually and form a virtual organization or virtual supply chain (VSC). In this research, we expand the traditional VSC concept to include the virtual and generic supply chain framework, which can generate specific supply chain configurations in order to solve the quotation response problem. This research addresses the quotation response problem for custom products via VSC network structure and configuration. An integrated method is proposed to generate quotations efficiently and accurately for custom products. A domain-based framework is employed to identify and coordinate the critical issues among product, process and virtual supply chain configuration to map the process of quotation response from customer domain to product domain and further down to supply chain domain. VSC configuration entails the instantiation of a generic supply chain network into various specific supply chain variants in accordance with diverse customer requirements. VSC manifests itself through the configuration of supply chain networks, in which a large number of entities and their interdependencies in relation to product platform families, process platforms and logistics networks are synchronized coherently. It emphasizes the conceptualization and formalization of the VSC to enhance the power of variety handling, with respect to supply chains as well as products and processes. By analyzing the tradeoffs among various objectives, a final supply chain configuration is selected as the one that leads to optimal or near-optimal results in terms of the selected criteria. To validate the practical feasibility and performance of the quotation response via VSC configuration, a case study of a global motor supply chain is developed based on the domain based structures and class concept. The integrated method is adopted to generate quotation response in a rapid and cost-effective way. The result of a case study based on an electrical motor, including supply chain performance in terms of cost and on-time delivery, has demonstrated the potential application of this integrated quotation response method. Although the configuration of actual global supply chains for custom products encompasses more issues than what presented in the case study, the fundamental ideas of the integrated method has been demonstrated and can be extended for practical decision making.